The Analysis of Teachers’ Written and Oral Questions in the Efl Classroom at Junior High School in Padang - Uswatun Hasanah Yude (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Teachers primarily ask questions in an EFL classroom to measure their students’ comprehension and stimulate their curiosity. Teachers can ask a wide variety of questions. Every question has a unique impact on the degree of thinking of the students. The goal of this study was to examine the most common questions that teachers in SMPN Kota Padang’s EFL classroom asked. This study is descriptive in design. It involved observing a subject and documenting their behavior, as well as using textual material from Geschool that was unchanged in any approach. The 18 teachers who were chosen for this study’s subjects were drawn at random from six different schools. Written questionnaires from Geschool and video recordings of classroom observations served as the data gathering methods. The study’s conclusions show that remembering (C1), which accounts for 155 questions (or 40.15 percent of all questions) and represents the lowest level of thinking in the cognitive domain, is the most frequently asked type of question by teachers in EFL classroom activities in SMPN Kota Padang.